Analysis of The Influence of Service Quality and Relationship Quality on Customer Satisfaction - Karimah, Aprilia Fitri; Ratnasari, Vita (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
PT. PLN (Persero) is one of the State-Owned Enterprises (BUMN) which aims to provide and serve customer needs for electric power. To improve efficiency, service quality, and electricity supply, PT. PLN (Persero) has transformed into four main focuses, namely Lean, Green, Innovative, and Customer Focused. At the point of Customer Focus, PT. PLN (Persero) especially UP3 Kendari has implemented a web-based system to manage complaints and reports of disturbances. The high level of public complaints, demanded PT. PLN (Persero) to improve services that have been provided to the community. It aims to build a good image in society. In this study, a theoretical model and 3 hypotheses were proposed to be tested using the SEM method. This study uses primary data by using data questionnaires to 150 customers. The results of the SEM analysis show that the service quality variable with a value of 0,832 is significantly and positively related to customer satisfaction. Otherwise, the relationship quality with a value of 0.030 has no significant effect on customer satisfaction. The relationship quality variable has an indirect effect on customer satisfaction through service quality of 0.739. To increase customer satisfaction, PLN needs to improve the quality of customer relationships.